Texture-driven reformulation of pork liver mousse with reduced allergenic components - Narcís Feliu-Alsina; Elena Saguer (Applied Food Research)
Since allergies associated with the consumption of pork are rare, this work proposes to use a pork liver extract with a neutral odour and excellent foaming properties both to reduce the presence of liver in the formulation of a mousse, thus minimising its strong impact on flavour, and as an alternative to egg due to its allergenicity. The results obtained showed that it was possible to replace up to 20 % of the liver in the initial formulation without affecting the mousse texture, and with a remarkable improvement in its olfactory characteristics. Although it was not possible to eliminate whole eggs due to the good emulsifying properties of the yolk, egg whites – i.e., the most allergenic egg fraction- could be completely replaced with liver protein extract. Next, to minimise the presence of allergens, the substitution of butter with different proportions of lard and pork backfat was tested. It was observed that pork backfat contributed to denser, harder and more consistent mousses than lard with no negative effects on the resistance to spread and adhesivity of mousses. But, considering the textural and olfactory characteristics of the mousses, it can be kept that including lard and pork backfat in a ratio of 60:40 was a suitable combination to replace butter.